2011
DOI: 10.1103/physrevb.83.035309
|View full text |Cite
|
Sign up to set email alerts
|

Circular photogalvanic effect on topological insulator surfaces: Berry-curvature-dependent response

Abstract: We study theoretically the optical response of the surface states of a topological insulator, especially the generation of helicity-dependent direct current by circularly polarized light. Interestingly, the dominant current, due to an interband transition, is controlled by the Berry curvature of the surface bands. This extends the connection between photocurrents and Berry curvature beyond the quasiclassical approximation where it has been shown to hold. Explicit expressions are derived for the (111) surface o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
238
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(243 citation statements)
references
References 32 publications
3
238
0
2
Order By: Relevance
“…This spin-locking property allows a circularly polarized light to generate a DC rectified current at the surface of the insulator. Recently, Pavan Hosur pointed out that this socalled circular photogalvanic effect (CPE) can be used as a detection of a finite Berry curvature [32]. Indeed, in presence of the latter there is a contribution to the photocurrent that grows linearly in time before being cut-off (by a scattering event) after some relaxation time.…”
Section: Topological Invariant and Photocurrentmentioning
confidence: 99%
See 3 more Smart Citations
“…This spin-locking property allows a circularly polarized light to generate a DC rectified current at the surface of the insulator. Recently, Pavan Hosur pointed out that this socalled circular photogalvanic effect (CPE) can be used as a detection of a finite Berry curvature [32]. Indeed, in presence of the latter there is a contribution to the photocurrent that grows linearly in time before being cut-off (by a scattering event) after some relaxation time.…”
Section: Topological Invariant and Photocurrentmentioning
confidence: 99%
“…5 Photocurrent induced within a 2D surface state We now discuss the potentialities of using circularly polarized light to probe the surface state (SS) of a threedimensional (3D) topological insulator, like Bi 2 Se 3 , Bi 2 Te 3 , or strained HgTe [32,33].…”
Section: Topological Invariant and Photocurrentmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many theoretical and experimental works in the past few years on helicity-controlled photocurrents [14][15][16][17][18], the linear photogalvanic effect [19][20][21], local photocurrents [22,23], edge photocurrents in two-dimensional (2D) TIs [24,25], coherent control of injection currents [26,27], photon drag currents [19,28,29], second-harmonic generation [30], photoinduced quantum Hall insulators [31,32], cyclotron-resonance-assisted photocurrents [33,34], quantum oscillations of photocurrents [35], photogalvanic currents via proximity interactions with magnetic materials [36][37][38], and the photoelectromagnetic effect [39]. These phenomena, scaling in the second or third order of the radiation electric fields, open up new opportunities to study Dirac fermions, which has been already demonstrated for graphene (for a review see Ref.…”
Section: Introductionmentioning
confidence: 99%